WIDOW STATUS IN THE VIEW OF THE COMMUNITY OF LATAWE VILLAGE, NAPANO KUSAMBI DISTRICT, WEST MUNA DISTRICT - Laxmi; Hartini; Zainal; Marsiah Sumule; La Ode Aris (Media Inovasi Pendidikan dan Publikasi, 2024)
The status of a widow in society is often defined in terms of various stigmas, ranging from factors to the impact felt by a wife after choosing this status. Therefore, this article was created with the aim of knowing and describing the views of the people of Latawe Village, Napano Kusambi District, West Muna Regency regarding the status of widows. The data analysis used in this research is descriptive qualitative with data collection techniques through observation and in-depth interviews. The results of these findings show that the people in Latawe Village have quite a high level of sympathy for women who are widows, as shown by divorced women who tend to have good behavior or a good personality. Thus, this view is also influenced by women with widow status who have a hardworking spirit who do not give up easily, and try to achieve the goal of becoming strong women and always have a positive attitude.